La inexigibilidad de requisitos al cargo de asambleístas en Ecuador y su respaldo en el Artículo 119 de la Constitución de la República - Caicedo Arroyo, Nandi Thais (2023)
He present work addresses the current problem of the designation for assembly member in Ecuador, the same one that is rooted in the legislative issue. The general context is an evident lack of parliamentary education so that Ecuadorians as citizens have the objective of being part of a sector. The historical methodology was developed, among the types of research used we have: historical, exploratory, descriptive, the approach used in the present investigation is: mixed, qualitative and quantitative, for the techniques and instruments the interview and survey were taken. The fundamental conclusion tells us that if there is evidently a widespread discontent of the population regarding the legislative system, either due to the poor participation of the assembly members elected by popular election, which demonstrates a lack of professional ethics to hold a position which is not is prepared, due to the existence of a profound lack of knowledge about its activities to be carried out..............